Perancangan Rantai Motor Suzuki Shogun FL 125 RCD Tahun 2007 - muhamad ghofur; Aa Santosa; Oleh oleh (Jurnal Ilmiah Wahana Pendidikan, 2023)
The chain is one of the components used to transfer power from the engine to the rear wheels. These components are needed to transmit power from the engine to the rear wheels. Chain components consist of inner and outer plates, bushes, pins and rollers. This study aims to determine how much load is needed to test the strength of the chain. The component that will be discussed is the Suzuki Shogun FL 125 RCD motorcycle chain. In this study using an analytical method, which uses equations based on previous research references. The results of the analysis show that the selected chain is roller chain no. 40, rear sprocket speed is 1225 rpm, front sprocket speed is 3470 rpm, chain speed is 6.8 m/s, chain force is 144.1 kg, chain length is 1470 mm, and the chain life is 1625 days or about 4.5 years.